The diffusion of edublogs among educators in Egypt - Abdelrehim, Salma Hany Mohammed Omar (AUC Knowledge Fountain, 2013)
This study gives some insight with regards to the diffusion of educational blogs among educators working in Egypt. Through the literature review the researcher establishes the importance of edublogs and gives examples of their use around the world, then goes on to answer questions about the reasons behind why edublogs are not being used by educators in Egypt. The research compares edublog adopters and nonusers by tackling three issues in the diffusion process. For the adopters, the study inquires about how they found out about the edublogs to see if it was traditional word of mouth as the diffusion of innovations theory suggests, and who told them about this innovation. The research also examines the hindrances keeping educators from using edublogs. And finally, the research labels the Egyptian educators in relevance to adopter categories.